Citizenship Education in the Framework of 2030 Agenda and Environmental Justice - M. Ángeles Murga-Menoyo (Universidad Autónoma de Madrid, 2018)
This article seeks to analyze the guidelines of Unesco for an education consistent with the Sustainable Development Objectives (sdo) set out in the agenda; identify their weaknesses and strengths for the education of a citizenship committed to environmental justice; and propose an alternative to remedy the deficiencies identified. A hermeneutic methodology has been used for the analysis of bibliography and documents. The results shown that Unesco's training guidelines do not exhaust the priority objectives that the environmental justice movement attributes to education, although they can contribute to them; the respective strengths of both approaches could lead to synergies with reciprocal beneficial effects. The article highlight the significant features of Agenda 2030 and the concept of environmental justice. The key competences in sustainability that Unesco proposes are analyzed next, and they are evaluated from the perspective of environmental justice. The fourth section is devoted to the type of citizenship that is required for the education considered in both approaches. Finally, we made an integrative proposal about the educational needs to achieve ods and environmental justice.